Assessing urban waterfront public space service quality using importance performance analysis (IPA) - Suminar, Lintang; Ramadhani, Difa Ayu Balqist; Endriyanto, Dhimas (ARTEKS : Jurnal Teknik Arsitektur, 2024)
The urge for urban public space evolved in increasingly dense cities. Tirtonadi Dam Park is a waterfront-designed urban park located on Bengawan Solo riverbank area. To support the activities, adequate infrastructure must be provided. The objective of this study was to assess Tirtonadi Dam Park's service quality as an urban public space and suggest methods to improve it to promote local communities' economic development. The variables—infrastructure, access & linkage, comfort & images, use & activity—were evaluated and compiled into 16 indicators. Based on user perceptions, Importance Performance Analysis (IPA) was employed to determine the performance and importance levels of predetermined variables. The findings demonstrated that vegetation, infrastructure for the disabled, and drainage and water systems all dropped into the "concentrate here" quadrant, necessitating further development to enhance quality and add more supporting facilities. Furthermore, the quality of security, environmental cleanliness, pedestrian paths, recreational facilities, informal sectors, lighting facilities, and transportation lies in the “keep up the good work” quadrant so that they should be maintained. Enhancing waterfront facilities with leisurely and recreational features can increase the number of visitors. Improving urban areas and incorporating the surrounding communities in all phases of development will be crucial, with the potential to enhance their economic circumstances.